New trends in sustainability reporting: Exploring the online sustainability reporting practices by Irish universities - Yanqi Sun; Dan Zhao; Yuanyuan Cao; Cheng Xu (Journal of Innovation & Knowledge (JIK), 2024)
This study is to understand the current status of online sustainability reporting (SR) practices by Irish universities. The paper reveals that online SR is in its infancy at the sample universities and there is significant room for improvement. Irish universities have initiated using web-based SR to inform their stakeholder groups, but they tend to report symbolic contents rather than substantive ones. The findings indicate that online SR practice by Irish universities is for the purpose of gaining legitimacy rather than satisfying the information needs of stakeholders. The assessment of online SR practices serves as a first step to help the universities use new technologies, in particular the internet, to improve the dialogue with stakeholders. This paper reminds universities that they should seek more than merely to meet the minimum acceptable level of online SR disclosure in society. The study will be of interest to university administrators, policymakers, regulators, and other stakeholder groups of universities.
Keywords: M41; O16; Q01; Q56; 650; Sustainability reporting; University; Online disclosure; Stakeholder theory; Legitimacy theory; Social impact